2017
DOI: 10.1148/rg.2017160175
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of US Artifacts

Abstract: Artifacts are frequently encountered at clinical US, and while some are unwanted, others may reveal valuable information related to the structure and composition of the underlying tissue. They are essential in making ultrasonography (US) a clinically useful imaging modality but also can lead to errors in image interpretation and can obscure diagnoses. Many of these artifacts can be understood as deviations from the assumptions made in generating the image. Therefore, understanding the physical basis of US imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 13 publications
1
68
0
Order By: Relevance
“…Secondly generated echoes will then reverse course along the same path. Since the ultrasound system makes the false assumption of a rectilinear course, the final image will be reconstructed beyond the reflective interface, thus giving a mirror artifact on both sides of the interface [21]. "Ghost" echoes may be located in the primary beam's axis or be laterally displaced.…”
Section: Mirrored Elastogram Artifactmentioning
confidence: 99%
“…Secondly generated echoes will then reverse course along the same path. Since the ultrasound system makes the false assumption of a rectilinear course, the final image will be reconstructed beyond the reflective interface, thus giving a mirror artifact on both sides of the interface [21]. "Ghost" echoes may be located in the primary beam's axis or be laterally displaced.…”
Section: Mirrored Elastogram Artifactmentioning
confidence: 99%
“…As can be appreciated, because of the random presence of multiple reflectors in the near field of the probe, including the scarred myocardial apex of our patient, multiple pathways be-tween the reflectors and the probe generate a stepladder reverberation, which in fact is similar to the well-known comet-tail and ring-down ultrasound artifacts. 3 Finally, the clutter in our patient is not generated by reverberations caused by interfering lung tissue, as this type of reverberation artifact fluctuates or displaces upon (forced) respiration, 7 which was not the case in our patient.…”
Section: Mechanism Of Nfcmentioning
confidence: 61%
“…Although tissue-harmonic imaging (THI) 1 and improved probe design over the past decades have significantly reduced ultrasound artifacts, they nevertheless remain an important issue in daily clinical practice and may lead to misdiagnosis or missed diagnosis. 2,3 The near-field artifact in our patient has been designated in the past as NFC, and this may be particularly challenging, as it may mimic a thrombus. 4 Misdiagnosis may expose the patient to the unnecessary bleeding risk of anticoagulative therapy.…”
Section: Discussionmentioning
confidence: 97%
“…We found that most angioleiomyomas showed posterior acoustic enhancement; to our knowledge, this finding has rarely been described. Posterior acoustic enhancement (or increased through‐transmission) refers to the increased intensity of echoes relative to surrounding tissues occurring distal to a low‐attenuating structure . Although posterior acoustic enhancement is seen in many cystic tumors, it is important to consider that it is frequently seen in angioleiomyomas.…”
Section: Discussionmentioning
confidence: 99%